Effectiveness of muscle energy technique (met) in patients with acute low back pain: Qusai experimental Study - Muhammad Usman Khalid; Danish Hassan; Yasir kazmi; Muhammad Hassan; Haroon Mansha; Hayatullah khalid (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Low back pain is a common problem in society. Acute low back pain can persist for up to six weeks and requires immediate attention for treatment. The muscle energy technique was mostly used in rehabilitation for strengthening and relaxation purposes. The objective of the study was to find out the effectiveness of the muscle energy technique in patients with acute low back pain.METHODOLOGY: It was a quasi-experimental trial; with a sample size of 60 were collected from 05 June 2020 to 05 November 2020. A convenient sampling technique was used and patients were divided into two groups after inclusion and exclusion criteria. The tools were the Standardized visual analog scale (VAS) and Oswestry disability index (ODI). The setting was Ibn e Siena Hospital and Research Institute, Multan and Multi-care physiotherapy clinic Multan. An Independent t-test was applied to measure the significance of data. The experimental group was treated by muscle energy technique and the control group was treated through neuromuscular control exercises.RESULTS: Total number of patients in the study was 60, equally divided into two groups. Pre and post control and experiment group ODI mean±SD 28.13±5.25, 12.66±3.78 and 26.13±4.12, 7.80±3.14, pre and post-VAS 8.70±0.79, 8.30± 1.17 and 2.00± 1.20, 0.76± 1.00 respectively. There was a significant difference (p<0.000) between a pre and post intervention score of the Oswestry disability index (ODI) and the visual analog scale (VAS).CONCLUSION: Muscle energy technique was more effective than neuromuscular control exercises in mechanical acute low back pain.